LVIV REGION AS A PROMISING REGION OF UKRAINE FOR SUSTAINABLE DEVELOPMENT OF TOURISM AND RECREATION (Development Service Industry Management, 2024)
The article is devoted to researching the tourism and recreation potential of Lviv Oblast, assessing the impact of modern challenges on the development of tourism in the region, and developing recommendations to ensure the sustainable development of the tourism sector in crisis conditions. In the process of research, the main problematic aspects and prospects of the transition of the region to the direction of sustainable development were established, and a SWOT analysis of the tourism and recreation sphere of the Lviv Region was carried out, which confirms that the development of tourism and diversification of the economy is key to the further success of the region. The main problems, ways to solve them, and prospects for the development of the region's tourism potential have been identified. It was established that the tourism development strategy should be aimed at creating new innovative products and improving infrastructure. In general, the development of tourism in the Lviv region requires a comprehensive approach and cooperation of all interested parties: authorities, businesses, public organizations, and international partners to ensure the sustainable and successful development of tourism in the Lviv region. Thus, the Lviv region has all the prerequisites to become one of the most attractive tourist destinations not only in Ukraine but also in the whole of Central and Eastern Europe.
Keywords: tourist and recreational resources; Lviv region; sustainable development; tourism; recreation; infrastructure